Study of sensitivity evaluation on ridgetail white prawn (Exopalaemon carinicauda) quality examination methods. Issue 1 (1st January 2019) - Zheng, Haonan; Ying, Xiaoguo; Wang, Wenxin; Chen, Zhenzhen; Shao, Chenning; Zhou, Huimin; Wang, Siyang; Ping, Xinyi; Li, Jian; Yi, Xiaomei; Deng, Shanggui; Hui, Guohua
ABSTRACT: In this paper, ridgetail white prawn ( Exopalaemon carinicauda ) quality evaluation was performed by electronic nose (e-nose). Physical/chemical, such as human sensory evaluation (HSE), weight loss, colour, total viable counts (TVC), GC-MS, K value, microbial, and e-nose were persistently tested. Principal component analysis (PCA) and stochastic resonance (SR) were used for measurement data processing. Results suggested that prawn quality persistently decreased due to microbial propagation. GC-MS results demonstrated that the volatile gases emitted by the samples increased during measurement. PCA could not discriminate all prawn samples, and SR eigen values discriminated all samples. Sensitivity evaluation on colour, TVC, weight loss, HSE, GC/MS, K value, and e-nose was made, and results indicated that e-nose presents some advantages including low cost, rapid examination, and good repeatability. E-nose Prawn quality evaluation model was also built for e-nose.